우리나라 논에서 발생한 제초제 저항성 잡초의 작용기구 - 최성환(Sung Hwan Choi); 신호용(Ho Yong Shin); 심수용(Soo Yong Shim); 정정성(Jung Sung Chung); 이상현(Sang Hyun Lee); 조광민(Kwang Min Cho); 홍점규(Jeum Kyu Hong); 이증주(Jeung Joo Lee) (Weed & turfgrass science, 2024)
일반적으로 제초제 저항성은 target-site resistance (TSR)와 non-target-site resistance (NTSR)로 구분할 수 있다. TSR 메카니즘은 제초제 target 단백질을 코딩하는 유전자의 돌연변이에 의해 해당 단백질과 제초제 분자와의 결합이 감소하거나, target 단백질의 과잉 생산에 의해 발생할 수 있다. NTSR은 TSR과 달리 제초제의 흡수, target 단백질 부위로의 이행 및 축적의 단계 중 적어도 하나를 저해하거나, 제초제의 유해 작용을 보상하는 메커니즘에 의해 유발된다. 또한, NTSR은 제초제의 반복 처리에 의해 저항성 관련의 대립유전자가 축적되어 진화하며, 그 결과 저항성은 더 높아진다. 이 중에서 cytochromes P450을 비롯한 여러 효소들은 제초제의 분해 및 저분자 화합물과의 포합 반응을 통하여 작용점 부위에서 축적되는 제초제의 양을 감소시키거나 제초제의 유해 작용으로부터 세포를 보호하므로, NTSR에서 가장 중요한 역할을 수행한다고 볼 수 있다. NTSR 저항성을 획득한 잡초는 다른 작용 기구를 가진 제초제에 대해서도 교차저항성을 발휘할 수 있으므로 TSR 저항성을 획득한 잡초보다 방제가 더 어렵다. 저항성을 획득한 잡초는 생장 적응을 위한 비용이 필요로 할 수도 있는데, 이러한 적응 비용을 다발성 발현 효과라 한다. 적응 비용과 관련하여 저항성 식물은 감수성 식물에 비해 종자 및 biomass의 생산, 경합 능력 및 발아 등이 불리하거나 드물게는 유리할 수도 있다. 2017년우리나라에서ALS저해제초제에대한저항성논잡초의발생면적은2012년에비해벼재배면적기준으로약2.8 배 이상 증가하였다. 10,000ha 이상 발생한 저항성 잡초 종도 2004년 3개, 2008년 4개, 2012년 7개, 2017년 8개로 증가하였다. 2012년까지는 100,000 ha 이상 발생한 저항성 잡초는 없었으나, 2017년에는 저항성M. vaginalis,Echinochloa spp. 및S. juncoides가 각각 292,936 ha, 180,753 ha 및 138,756 ha나 발생하였다. 2013-2015년에 걸쳐 전국에서 채집된E. oryzicola 에서도ACCase 및ALS 저해제에 대한 저항성 및 교차저항성이 발생하였다. ALS 저해제에 대한 저항성은M. korsakowi 의 경우 als 유전자의 주요 변이 부위인 197Pro(CCT)이 아닌 다른 부위의 변이에 의해서, M. vaginalis 및 S. trifolia에서는197Pro(CCT)의 변이에 의해서 유기되었다. 또한, 일부 S. juncoides의 저항성 biotype도 197Pro의 변이에 의해 낮은 정도의저항성을 나타냈다. 이와 같은 결과로부터M. korsakowi,M. vaginalis,S. trifolia 및 일부S. juncoides의 저항성은TSR 메커니즘에 의해 유기된 것으로 사료되었다. 한편, 또 다른 저항성S. juncoides GS28은als 유전자의 돌연변이가 일어나지 않았음에도 불구하고 강한 저항성을 나타내었으나, P450의 저해제인 fenitrothion 처리에 의해 저항성이 현저하게 감소하였음으로, NTSR에 의해 저항성이 유기된 것으로 사료되었다. 저항성이 TSR에 의해 유기된 것으로 보이는S. trifolia는종자발아율에서감수성biotype보다유리한생장적합도를나타내었으며,종자에서유래된유식물의생장도촉진되었다. 그러나, 저항성S. trifolia의 괴경에서 유래된 유식물은 생장이 억제되었음으로, 유식물의 생장에 있어서는 저항성 및 감수성biotype간에상반된적합도를나타내는것으로사료되었다.현재까지우리나라에서는다수의ALS및ACCase저해제초제저항성잡초의발생이보고되었다.그러나,M. korsakowi,M. vaginalis,S. trifolia 및S. juncoides에서만target단백질유전자의 변이 여부가 밝혀졌다. 따라서 제초제 저항성의 구명을 위해서는 분자생물학적 연구를 통하여 더 많은 저항... In general, herbicide resistance can occur by target-site resistance (TSR) and non-targetsite resistance (NTSR) mechanisms. The TSR mechanism can occur by mutations in genes encoding herbicide target proteins, which decrease the binding of the protein to the herbicide molecule, or by overproduction of the target protein. Unlike TSR, NTSR is induced by mechanisms that inhibit at least one of the steps of herbicide uptake, translocation to the target protein site, and accumulation, or by compensating for the harmful effects of herbicides. In addition, NTSR evolves by accumulating resistance-related alleles through repeated herbicide treatment, resulting in higher resistance. Among these, several enzymes including cytochromes P450 can play the most important role in NTSR by reducing the amount of herbicide accumulated at the site of action through herbicide decomposition and conjugation reaction with low-molecular-weight compounds, or protecting cells from the harmful effects of herbicides. Weeds that have acquired NTSR resistance can also exhibit cross-resistance to herbicides with different mechanisms of action, making control more difficult than weeds that have acquired TSR resistance. Weeds that have acquired resistance usually require costs for growth adaptation, and these adaptation costs are called pleiotropic effects. In relation to adaptation costs, resistant plants may be disadvantaged or, in rare cases, advantageous compared to susceptible plants in terms of seed and biomass production, competitive ability, and germination. In 2017, the area of resistant paddy weeds to ALS-inhibiting herbicides in Korea increased by about 2.8 times compared to 2012 based on the rice cultivation area. The number of resistant weed species that occurred over 10,000 ha also increased from 3 in 2004 to 4 in 2008, 7 in 2012, and 8 in 2017. Until 2012, there were no resistant weeds that occurred over 100,000 ha, but in 2017, resistant Monochoria vaginalis, Echinochloa spp., and Scripus juncoides occurred in 292,936 ha, 180,753 ha, and 138,756 ha, respectively. Resistance and cross-resistance to ACCase and ALS inhibitors were also observed in Echinochloa oryzicola collected nationwide from 2013 to 2015. Resistance to ALS inhibitors was induced by mutations in sites other than the major mutation site 197Pro (CCT) of the als gene in Monochoria korsakowi, and by mutations in 197Pro (CCT) in M. vaginalis and Sagittaria trifolia. In addition, some resistant biotypes of S. juncoides also showed low levels of resistance due to mutations in 197Pro. From these results, it is considered that the resistance of M. korsakowi, M. vaginalis, S. trifolia, and some S. juncoides was induced by the TSR mechanism. Meanwhile, another resistant S. juncoides GS28 showed strong resistance despite the absence of mutation in the als gene, but the resistance was significantly reduced by treatment with fenitrothion, a P450 inhibitor, suggesting that the resistance was induced by NTSR. S. trifolia, whose resistance appeared to be induced by TSR, showed more favorable growth f itness than the susceptible biotype in terms of seed germination rate, and the growth of seedlings derived from the seeds was also promoted. However, the growth of seedlings derived from tubers of resistant S. trifolia was inhibited, suggesting that the resistant and susceptible biotypes showed opposite fitness in terms of seedling growth. To date, the occurrence of many ALS and ACCase-inhibiting herbicide-resistant weeds has been reported in Korea. However, mutations in the target protein gene were only revealed in M. korsakowi, M. vaginalis, S. trifolia, and S. juncoides. Therefore, in order to elucidate herbicide resistance, it is essential to identify mutations in the target protein in more resistant weed species through molecular biological studies. In addition, it is necessary to establish measures that can be used to prevent the occurrence of herbicide-resistant weeds and control already... KCI Citation Count: 0